Development of an on-line temperature-assisted ionic liquid dispersive microextraction system for sensitive determination of vanadium in environmental and biological samples - Berton, Paula (2010)
An original flow injection (FI) system was developed for on-line microextraction of Vanadium (V) based on room temperature ionic liquid (RTIL). Vanadium was complexed with 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP) at pH 4.0. A 40 uL-volume of 1-butyl-3-methylimidazolium hexafluorophosphate ([C4mim][PF6]) RTIL was mixed with 5mL of sample solution containing the V-5-Br-PADAP complex. Then, a fully on-line temperature-assisted dispersion procedure was developed, followed by, analyte microextraction;  and final on-line separation of the RTIL phase with a florisilcontaining microcolumn. Vanadium was removed from the microcolumn with a 10% (v/v) nitric acid (in acetone) solution, and finally measured by electrothermal atomic absorption spectrometry (ETAAS). The detection limit achieved after preconcentration of 5mL of sample solution, was 4.8 ng/L. The relative standard deviation (RSD) for 10 replicate determinations at 5 ug/L of vanadium level was 4.1%, calculated from the obtained peak heights. The calibration graph was linear, with a correlation coefficient of 0.9982 at levels from the detection limits up to 15 ug/L. The method was successfully applied for the determination of vanadium in environmental and biological samples.